La caverna nel bosco - Maxia, Michela (Milano University Press, 2021)
The book is part of an action-research project (MinViTI) dedicated to the accompaniment and support of youngsters who have a family member hospitalized in ICU. The book is designed for children aged 6 to 10 and their parents, so that, through the story of the Leo bear and his mother - cared for by the animals in the cave in the forest - they can find a way to recognize and share their emotions, activate resources and prepare for a possible visit to the Intensive Care Unit. The book is promoted in collaboration with the Intensive project, it, a scientific initiative supported by SIAARTI, ANIARTI, AAROI-EMAC, dedicated to the humanization of ICU care.